Pengaruh Literasi Akuntansi dan Flourishing Terhadap Komitmen Patuh Pajak Dengan Kebutuhan Kompetensi Perpajakan Sebagai Pemoderasi - Tambun, Sihar; Parago, Agnes Do; Sitorus, Riris Rotua (Media Akuntansi Perpajakan, 2023)
This research is about "The Effect of Accounting Literacy and Flourishing on Commitment to Tax Compliance with the Need for Tax Competence as a Moderation". This research is motivated by the fact that there are still many Indonesian people who are still not compliant in paying taxes. This researcher uses four variables consisting of variable Y) Commitment to Tax Compliance as the dependent variable. Variables X1) Accounting Literacy and X2) Florishing are independent variables. Next, variable Z) Tax Competency Needs as a moderating variable. This research aims to prove whether there is an influence of accounting literacy and growth on commitment to tax compliance which is moderated by Tax Competency Requirements. The research design uses causality which aims to test the direct effect and moderating effect between variables. The software used is SmartPLS (Partial Least Square). The results of this research are First, it shows that Accounting Literacy has no significant effect on Tax Compliance Commitment, which means that based on this, the hypothesis in this research is rejected. Second, Flourishing has a significant effect on Tax Compliance Commitment, which means that based on this, the hypothesis in this research is accepted. Third, it is stated that the Tax Competency Requirement has a significant effect on the Commitment to Tax Compliance. Which means that based on this, the hypothesis in this research is accepted. Fourth, the need for Tax Competency strengthens the relationship between Accounting Literacy and Commitment to Tax Compliance and has a significant effect, which means that based on this, the hypothesis in this research is accepted. Fifth, the need for Tax Competency strengthens the relationship between Flourishing and Tax Compliance Commitment and does not have a significant effect, which means that based on this, the hypothesis in this research is rejected.